Investigating the Relationship between School Culture and Academic Enthusiasm with Academic Hope and Motivation in High School Students - Sophia Khaneghahi; Sajad Sefatgol; Malihe Siyasar (Journal of Social, Humanity, and Education, 2022)
Purpose: The aim of this study was to investigate the relationship between school culture and academic enthusiasm with academic hope and motivation in high school students. Research methodology: The present study is applied in terms of purpose and is among the descriptive studies of correlation type. The statistical population includes all high school students in Zahak city,whose number in the academic year 2021-2022 is 1324 people.Using Morgan table and Cochran's formula, 297 students were selected by statistical random sampling as a statistical sample.To prevent statistical sample loss and better adequacy, a sample of 320 questionnaires was distributed by multi-stage random cluster sampling method. Results: The results of the analysis showed that there is a positive and significant relationship between academic motivation and students' academic enthusiasm.The intensity of this relationship is very strong and academic motivation has the power to predict academic enthusiasm. There is no significant relationship between school culture and academic motivation and school culture does not have the power to predict academic motivation. Limitations: What should be considered by school parents is to pay attention to creating a correct and flexible culture in school, because each student spends more than half of his time in school and is exposed to school relationships and culture, and these relationships over time. Contribution: Among the limitations of the research are the lack of sufficient scientific content around the research variables,the lack of cooperation of some schools in the implementation of the questionnaire and the limitation in the generalizability of the results of this research.